Pengaruh Rasio Keuangan Early Warning System terhadap Tingkat Solvabilitas Perusahaan Asuransi Jiwa Syariah Periode 2010-2013 - Utami, Ely Pramuji; Khoiruddin, Moh (Management Analysis Journal, 2016)
The purpose of this research is to investigate the influence of liquidity ratio, retention, expense ratio, and the size of the company to the company’s solvability rate that proxied by the ratio of risk-based capital (RBC). Samples of thr research was sharia life insurance companies that publish financial statements in 2010-2013. There were 40 samples in this research by using purposive sampling method. This research is a quantitative research. This research uses multiple linear regression. The results of this research shows that the expense ratio give significant affect to solvability rate of sharia life insurance company with a significance value of less than 0.05. While the liquidity ratio, the ratio of own retention and company size does not affect the company's solvability rate. The Advice given to investors who would buy insurance products do not need to pay attention to the liquidity ratio, and the size of the company's own retention in assessing the solvability rate of sharia life insurance company's as the third ratio did not affect the solvability rate. The Suggestions for the company is to maximize premiums in order to cover expenses due to the company expense ratio affect the solvency rate.